Dziedzictwo kulturowe jako kluczowe pojęcie edukacji regionalnej. Rozważania terminologiczne - Odoj, Grzegorz (Studia Etnologiczne i Antropologiczne, 2012)
It is impossible not to see consequences deriving from the lack of precision of the meaning of cultural heritage and notions connected to it in view of education called regional. It is easy to notice that cultural heritage both in ministry acts, publications on regional education and teachers’ and regionalists’ discourses is fairly freely used or even put in the form of imprecise generalities. An excessive inclination for differentiating between meanings ascribed to cultural heritage makes it very fluid and ambiguous. A characteristic of this phenomenon is a constant appearance of its new social and cultural features, which makes it difficult to predict its potential future specificity. If no significant processes of the destabilization of social life take place, we will witness the birth of a new content constituting cultural heritage. In this context, regional education is given a special role, whose one of the key tasks should be preparing the young for making a national evaluation of the cultural heritage content (yet it contains both the resources of the good and the evil), and making conscious choices therein in order to make them transform and adjust cultural heritage to the current needs in the future in a rational and reasonable way.